Enhanced performance of immobilized Rhizopus oryzae lipase on coated porous polypropylene support with additives - Sani, Fatimah; Mokhtar, Nur Fathiah; Mohamad Ali, Mohd Shukuri; Raja Abd Rahman, Raja Noor Zaliha (Multidisciplinary Digital Publishing Institute, 2021)
The immobilization of Rhizopus oryzae lipase (RoL) by hydrophobic adsorption on polypropylene supports with additives was investigated. Additives such as hen egg albumin, sodium caseinate and CAVAMAX® W6 were used to coat the support during immobilization where the immobilized RoL on coated support was compared to those of noncoated support. Following the immobilization, the catalytic activity of immobilized RoL was characterized based on different temperatures and pH. The immobilized RoL without additives showed optimal lipase activity at an optimum temperature of 50 °C and pH 6. However, RoL lipase that was immobilized on support treated with CAVAMAX® W6 had better performance in terms of hydrolytic activity and stability as compared to other additives. In addition, by having a support treated with hen egg albumin, the immobilized RoL was capable of yielding higher ester during esterification reactions.